1992
DOI: 10.1103/physrevlett.68.2192
|View full text |Cite
|
Sign up to set email alerts
|

Reconstruction of the Pt(111) surface

Abstract: The structure of the clean Pt(l 11) surface has been studied between 300 K and 0.92T m (T m =2045 K) via x-ray scattering. The surface is unreconstructed for temperatures less than 0.65T nu but reconstructs at higher temperatures to form a layer isotropically compressed and incommensurate with the underlying bulk (111) planes. A disordered arrangement of discommensurations separates regions with ideal fee stacking from regions with faulted stacking. With increasing temperature both the compression of the surfa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
78
0

Year Published

1994
1994
2013
2013

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(83 citation statements)
references
References 19 publications
(21 reference statements)
5
78
0
Order By: Relevance
“…Since the atomic spacing is less for the pure metal than for the III-nitride (3.19 Å vs. 2.8 Å for GaN compared to Ga, and 3.11 Å vs. 2.86 Å for AlN compared to Al), it is thus surmised that the metal overlayers contain the Ga or Al atoms with an interatomic spacing approximately the same as in the pure metal. At room temperature the arrangements thus form the complex nearly incommensurate structures seen in the diffraction patterns, reminiscent of the incommensurate surface structures of Au or Pt(111) 30 or of inert gases adsorbed on those surfaces. 31 At typical growth temperature the metallic overlayers are generally disordered, i.e.…”
Section: Aln(0001)mentioning
confidence: 99%
“…Since the atomic spacing is less for the pure metal than for the III-nitride (3.19 Å vs. 2.8 Å for GaN compared to Ga, and 3.11 Å vs. 2.86 Å for AlN compared to Al), it is thus surmised that the metal overlayers contain the Ga or Al atoms with an interatomic spacing approximately the same as in the pure metal. At room temperature the arrangements thus form the complex nearly incommensurate structures seen in the diffraction patterns, reminiscent of the incommensurate surface structures of Au or Pt(111) 30 or of inert gases adsorbed on those surfaces. 31 At typical growth temperature the metallic overlayers are generally disordered, i.e.…”
Section: Aln(0001)mentioning
confidence: 99%
“…Recently, it has been found that clean (111) oriented Pt surfaces reconstruct above 0.65 Tm, where Tm is the melting temperature [61]. The reconstruction can be described as a continuous commensurate-incommensurate transformation in which the surface layer is isotropically compressed relative to the underlying bulk lattice.…”
Section: Surface Reconstructions Of Clean Metal Surfacesmentioning
confidence: 99%
“…Further minimization of a (very small) strain energy associated with the anisotropy of the stress relief in the soliton reconstruction leads to a secondary ("herringbone") structure of the solitons [11]. Despite the general consensus that the soliton reconstruction is driven by the large tensile stress [12,13] on the Pt(111) [4][5][6]14] and the Au(111) surfaces, there is no direct experimental evidence, e.g., by measurements on the stress relief in the reconstruction.On the reconstructed (100) surfaces of Ir, Pt, and Au, the surface atoms form quasi-hexagonal (hex) commensurate and incommensurate overlayers. The atom density in the surface layer is higher by (20-25)%.…”
mentioning
confidence: 99%
“…On the (111) surfaces, the reconstruction involves a nonuniform compression of the surface along the [110] direction, with soliton-type domain walls between areas where surface atoms occupy fcc or hcp surface sites [2][3][4][5][6]. The reconstruction has been discussed frequently using the Frenkel-Kontorova (FK) model [7][8][9][10]: In the onedimensional (1D) version, a chain of atoms (representing the top layer) linked by springs with nearest-neighbor force constant w 00 and "natural" spacing b is placed in a sinusoidal potential with amplitude W ͞2 representing a rigid substrate with periodicity a.…”
mentioning
confidence: 99%